The World is Not Yet Flat : Transport Costs Matter! - Behrens, Kristian; Brown, W. Mark; Bougna, Theophile (World Bank, Washington, DC, 2016)
The paper provides evidence of the effects of changes in transport costs on the geographic concentration of industries. The analysis uses micro-level commodity flow data and micro-geographic plant-level data to construct industry-specific ad valorem trucking rates and continuous measures of geographic concentration. The findings show that, controlling for international trade exposure and input-output links, increasing trucking rates are significantly associated with declining geographic concentration. The effect is large: changes in trucking rates explain around 20 percent of the observed decline in geographic concentration of Canadian manufacturing industries between 1992 and 2008.